Characteristics of interconnections of construction sector and environment: regional study of Ukraine - Anatoliy Mokiy; Yuriy Pynda; Olha Ilyash; Mariia Pikh; Rostyslav Pynda (Przegląd Naukowy Inżynieria i Kształtowanie Środowiska, 2021)

(untitled)
The proposed modelling of the relationship between the spatial and component structure of the construction industry development and the environment helped to obtain combinations of high and medium levels of the impact of integral indicators of labour, productive and foreign economic components of the construction sector on the environmental index of the region. The high level of adaptability of the models used for the period 2013– –2018 confirms the relationship between the development of the construction sector in most regions of Ukraine and the lowest level of the ecological index. This proves the scientific hypothesis about the negative impact of construction on the country’s ecosystem. The study indicates that the dynamic characteristics of the relationship between the building system and the environment should take into account the existence of direct and indirect or even “hidden” relationships between the components. The scientific value of the study consists in using models of fuzzy sets to assess the relationship between the construction system and the ecosystem based on defuzzification, which preserves the flexibility of the process of assessing the development of subsystems in construction and making decisions as to reducing the negative environmental impact in regions.